2021
DOI: 10.3390/nu13041346
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide and Its Biobehavioral Correlates in Autism Spectrum Disorder: A Systematic Review of Human and Animal Evidence

Abstract: Autism spectrum disorder (ASD) pathophysiology is not completely understood; however, altered inflammatory response and glutamate signaling have been reported, leading to the investigation of molecules targeting the immune-glutamatergic system in ASD treatment. Palmitoylethanolamide (PEA) is a naturally occurring saturated N-acylethanolamine that has proven to be effective in controlling inflammation, depression, epilepsy, and pain, possibly through a neuroprotective role against glutamate toxicity. Here, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Palmitoylethanolamide (PEA) was chosen for this patient, as a targeted intervention for decreasing CCL2. This particular intervention was chosen because of the published studies noting benefits in children with ASD [49]. The patient's genomic results also reinforced what was seen in the labs regarding other specific nutritional deficiencies.…”
Section: Cds Genomic Results and Interpretationmentioning
confidence: 92%
“…Palmitoylethanolamide (PEA) was chosen for this patient, as a targeted intervention for decreasing CCL2. This particular intervention was chosen because of the published studies noting benefits in children with ASD [49]. The patient's genomic results also reinforced what was seen in the labs regarding other specific nutritional deficiencies.…”
Section: Cds Genomic Results and Interpretationmentioning
confidence: 92%
“…In the absence of human studies, no conclusions can be drawn about the relevance of PEA for the different clinical phenotypes of epilepsy. While limited evidence supports a neuroprotective effect of PEA against neuroinflammation and glutamate toxicity in the context of different neuropsychiatric conditions [ 13 ], studies are needed to elucidate the exact mechanism of action of PEA in epilepsy. Caution is needed about the finding of reduced PEA tone in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…It is an endogenous fatty acid amide, which exerts its biological effects through the activation of peroxisome proliferator-activated receptor-α (PPAR-α) and its related independent pathways, including ion channels involved in neuronal firing and the Transient Receptor Potential Vanilloid 1 (TRPV1) receptor [ 8 ], whose role is considered crucial in the fulfilment of neuroprotective, anti-inflammatory, and analgesic properties [ 9 ]. PEA has been suggested as an effective treatment for inflammatory disorders and pain [ 10 , 11 ], together with possible therapeutic implications in depressive symptoms and autism spectrum disorder [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the methodological heterogeneity of the studies ( Table 1 ) included in this review, risk of bias and study quality assessments were conducted with a reasonably inclusive and flexible approach, in line with previous research in the field ( 15 , 53 ). To this extent, interventional and observational studies in humans were evaluated through an adapted set of criteria suggested by the Agency for Healthcare Research and Quality (AHRQ) guidance ( 54 ), and risk of systematic bias across human studies was further ruled out by screening all papers for potential confounding variables, such as patients' age and educational level ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%